Economic Civil Society: Subjects of Social Economy - Kaczocha, Włodzimierz; Sikora, Jan (Studia Oeconomica Posnaniensia, 2015)
This paper presents a theoretical concept of civil society: its origins, understanding of this society, its four forms, including the developing civil society and its entities developed within the social economy, with the forms of foundations, associations and social cooperatives that operate in the region of Greater Poland. The study presents the thesis that, when the contemporary theory of social economy is developed, its creators will be able to adopt, from the theorists of the social economy developed in the interwar period, the view that the economy should aim to achieve the physical goals connected with cultural and ethical values. The paper is an analysis of related literature and secondary materials.